FRAMING NEWS ABOUT INDONESIAN CAPITAL CITY TRANSLOCATION BY ONLINE MEDIA OKEZONE.COM AND VIVA.CO.ID - Pradyanti, Alifia; Venus, Antar; Mahdalena, Vina (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
This study discusses how online media Okezone.com and Viva.co.id frame the news of the Moving of the Indonesian Capital. The research approach used is descriptive qualitative using framing theory. The method used is the Zhongdan Pan and Gerald M. Kosick Model. The model analyzes with four structures namely Syntax (title, lead, background information, source and closing quotes) Scripts (completeness of 5W + 1H news items), Thematic (paragraph propositions between sentences) and Rhetorical (words, idioms, pictures/photographs). This study uses document study data collection techniques originating from uploads of both online media in July-September 2019 related to the Moving of the Indonesian Capital so that six news were collected that were examined as a data analysis unit in this study. The findings obtained from the syntactic structure of the two media use the opposite title, whereby the background information used by Okezone.com is more to the government while Viva.co.id is more to the public. In the structure of the script Okezone.com fulfills the news element, but the resource persons chosen are only one point of view, while Viva.co.id has not fulfilled the news element in the third news. In the thematic structure the two media differ in highlighting their contents even with the same theme. For the rhetorical element, the use of images in both media is sufficient to explain the contents of the news. It is hoped that further research can emphasize media ideology in framing an event. In addition, the media can also display more than one resource so that it can be seen from various points of view. The community itself is expected to dig deeper information by not only from one media.